Assessment of Combined In-Plane and Out-of-Plane Fragility Functions for Adobe Masonry Buildings in the Peruvian Andes - Sumerente, Giovanni; Lovon, Holger; Tarque, Nicola; Chácara, César (Frontiers in Built Environment, 2020)
In the city of Cusco and in other parts of Peruvian andes, adobe masonry is the primarily construction material. Adobe continues being used for the construction of housing due to its low cost, its thermal properties, the use of unskilled labor as well as the local traditions of the Peruvian highlands. The Peruvian National Statistics Office (INEI) estimates that 67% of rural housing in Cusco is made of adobe masonry. Besides, previous seismic events and laboratory tests demonstrated that adobe dwellings without reinforcement are prone to collapse during an earthquake. Therefore, seismic vulnerability assessment of this type of dwellings is necessary aiming at developing proper contingency and mitigation risk policies. Then, fragility curves constitute a key tool when conducting seismic loss assessment since they provide information regarding the probability of exceeding a certain damage Limit State (LS) as a function of a given engineering demand parameter. This work aims at developing fragility curves, combining in-plane and out-of-plane loading conditions, for typical adobe buildings located in the city of Cusco. Initially, a set of one and two-story adobe houses were studied to determine the geometrical characteristics of representative local building typologies. Subsequently, 1000 artificial buildings were generated by means of Monte Carlo simulation based on the information gathered. The structural capacity of each artificial building was represented by simplified bilinear and trilinear capacity curves for in-plane and out-of-plane mechanisms, respectively. In order to represent the characteristics associated with subduction processes a set of ground motion records was established. The damage state of each building was assessed for each seismic record, and this information was collected into a Probability Damage Matrix (DPM). Finally, fragility curves were fitted for each damage state of the cumulative DPM. Preliminary results show that one and two-story adobe dwellings have a probability of collapse of 30% and 60%, respectively, when considering a peak ground acceleration (PGA) of 0.30 g, which corresponds to the expected acceleration related to a return period of 475 years over a soil type 2 according to the Peruvian Standards.